Consumers' perception of environmental and health benefits, and consumption of organic vegetables in Bangkok - Sansern Srinieng; Gopal B. Thapa (Agricultural and Food Economics, 2018)
Factors influencing consumers' perception of environmental effects of organic agriculture, and health benefits and consumption of organic vegetables were determined using linear regression analyses of primary data collected through consumers' survey in Bangkok. Results revealed that household income, respondent's age and gender, access to information on organic vegetables, household members with health problems and location of residence in suburban area had significant positive influence on consumers' perceptions of environmental effects of organic agriculture and health benefits of organic vegetables. Perceptions of environmental effects of organic agriculture and health benefits of organic vegetables, organic vegetable prices, organic vegetable stores accessibility, and household income had significant positive influence on consumption of organic vegetables. Child in household had significant negative influence on consumption of organic vegetables, and causes are given. Relevant policy recommendations include creating effective consumers' awareness of health and environmental benefits of organic vegetables and wider promotion of organic vegetables consumption.
Keywords: 330; Organic vegetables; Perception of environmental benefits; Perception of health benefits; Consumption; influencing factors; Bangkok